2020
DOI: 10.3390/foods9060700
|View full text |Cite
|
Sign up to set email alerts
|

Composition, Mineral and Fatty Acid Profiles of Milk from Goats Fed with Different Proportions of Broccoli and Artichoke Plant By-Products

Abstract: In the Mediterranean region, artichoke and broccoli are major crops with a high amount of by-products that can be used as alternative feedstuffs for ruminants, lowering feed costs and enhancing milk sustainability while reducing the environmental impact of dairy production. However, nutritional quality of milk needs to be assured under these production conditions and an optimal inclusion ratio of silages should be determined. This work aimed to evaluate the effect of three inclusion levels (25%, 40%, and 60%) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 48 publications
(54 reference statements)
0
11
0
Order By: Relevance
“…Analysis of the milk fatty acid profile was carried out in duplicate, with an extraction using the Folch method with some variations reported in Romeu-Nadal et al [ 33 ] and a subsequent methylation according to the method of Nudda et al [ 34 ], similar to what was done by Monllor et al [ 21 ]. The chromatograph, the column and the FAME mix for the identification of the milk fatty acids were the same as those used in the diets.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of the milk fatty acid profile was carried out in duplicate, with an extraction using the Folch method with some variations reported in Romeu-Nadal et al [ 33 ] and a subsequent methylation according to the method of Nudda et al [ 34 ], similar to what was done by Monllor et al [ 21 ]. The chromatograph, the column and the FAME mix for the identification of the milk fatty acids were the same as those used in the diets.…”
Section: Methodsmentioning
confidence: 99%
“…Silages were manufactured with a baler-wrapper (Agronic MR 820, Netherlands), with a weight of 300 kg and without additives, according to the work published by Monllor et al [14]. All rations were calculated according to the formulation recommendations of Fernández et al [21]. They were isoenergetic and isoproteic and the daily amount offered was 2.22 kg DM/day.…”
Section: Experimental Designmentioning
confidence: 99%
“…Relative to milk yield, ABS60 presented a significant lower yield value (1.91 kg/day), without varying the fat and protein content, which led to lower FCM and FPCM contents (p < 0.05) in ABS60 than in the other treatments with ABS (2.00 and 1.87 kg/day). With the lowest levels of ABS (25 and 40%), significant differences versus C for milk yield, LSCC, FCM and FPCM were not observed, as occurred in Monllor et al and Monllor et al [10,36], with 25% of ABS or artichoke plant silage in the diet of dairy goats, respectively. The lack of effect of the ABS diet on milk composition is as reported by Muelas et al [14].…”
Section: Body Weight and Milk Yieldmentioning
confidence: 73%
“…One of the salient features of using hot smoking with Oak sawdust was that HDPS possessed higher concentrations of fatty acids including MUFAs and PUFAs. Fatty acid is an important nutritional component that provides promising health benefits [39]. The study revealed a higher amount of omega-3 fatty acids, particularly DHA and EPA, found in hot smoked HDPS products, which are known to be effective in mitigating the onset of neurodegenerative complications in central nervous system neurons, cardiovascular disease progression, and arthritis [40][41][42].…”
Section: Discussionmentioning
confidence: 99%